Digital Communication and its Impact on the Process of Social Interaction Among Jordanian Youth - Al-Adra, Ibrahim Ahmed; Al-Tarawneh, Haya Husain; Al-Zeqef, Enas Ghassan; Younes, Duha Samir (Dirasat: Human and Social Sciences, 2026)
Objectives: This study aimed to examine the impact of digital communication on social interaction among Jordanian youth, focusing on its media, emotional, and interactive effects, as well as its influence on virtual identity formation. Method: A social sample survey was conducted with 504 young men and women, selected through convenience sampling. Data were collected using a questionnaire. Results: The study revealed that digital communication plays significant media and intellectual roles, enabling recipients to access information anytime and anywhere via various internet platforms. Emotional and behavioral influences were evident, as digital communication fosters emotional engagement with shared content. Regarding interactive and social compensation roles, digital communication allows individuals to achieve virtually what they might not accomplish in reality, a phenomenon termed "imaginative reality." Furthermore, the formation of virtual identity was observed, where assumed identities facilitate communication in unrealistic social contexts, potentially leading to harmful practices such as excessive gaming, identity fabrication, and withdrawal from the real world. Conclusions: The study recommends implementing social regulatory policies and legislation to monitor and counteract digital media rumors targeting youth. It also emphasizes promoting positive cultural dimensions and values.